Synthesis and characterisation of rice husk ash silica drug carrier for α-mangostin - Iqbal, Anwar; Shuib, Nur Azfa; Darnis, Deny Susanti; Miskam, Mazidatulakmam Akmam; Abdul Rahman, Nur Ruzaina; Adam, Farook (Penerbit Universiti Sains Malaysia, 2018)
The potential of rice husk ash (RHA) silica prepared via sol-gel method (RHA-Si) as a drug carrier was investigated. The nitrogen adsorption-desorption isotherm of RHA-Si indicates the presence of mesopores and some small percentage of micropores. The Brunauer, Emmett and Teller (BET) surface area of RHA-Si was 589 m2 g–1 and the Barrett-Joyner-Halenda (BJH) pore size was 5.1 nm. The adsorption of α-mangostin was confirmed by Fourier transform infrared (FTIR) spectroscopy and thermogravimetric analysis (TGA). The sample containing α-mangostin was labeled as RHA-Si-α. The BET surface area of RHA-Si-α was 110 m2 g–1 with the BJH pore size of 24.4 nm. The X-ray powder diffraction (XRD) showed that the RHA-Si and RHA-Si-α were amorphous. The disappearance of crystallinity of α-mangostin indicates that the solubility and dissolution of α-mangostin have been improved. The drug release profile indicated a burst release corresponding to 47% of the total drug loading in the first 15 min. The burst release was caused by physically adsorbed drug molecules. The findings suggest that RHA silica has potential application as nano drug carrier.